Determining Profitable Forage Rotations - J. Holman; A. Obour; A. Schlegel; T. Roberts; S. Maxwell (Kansas Agricultural Experiment Station Research Reports, 2019)
Annual forages are an important crop in the High Plains, yet the region lacks recommended annual forage rotations compared to those developed for grain crops. Forages are important for the region’s livestock and dairy industries and are becoming increasingly important as irrigation capacity and grain prices decrease. Forages require less water than grain crops and may allow for increased cropping system intensity and op-opportunistic cropping. A study was initiated in 2012 at the Southwest Research-Extension Center near Garden City, KS, comparing several 1-, 3-, and 4-year forage rotations with no-tillage and minimum-tillage. Data presented are from 2013 through 2018. Tillage generally increased winter triticale yields by 700 lb/a or 30% compared to no-till yields, due largely to increased plant available water. Plant available water at planting winter triticale averaged 5.9 in./a in min-till and 3.9 in./a in no-till. Double-crop forage sorghum yielded 17% less than full-season forage sorghum and yields were not affected by tillage. Oat yields were lower than forage sorghum or winter triticale, averaging 2,100 lb/a across years. Subsequent years will be used to further compare forage rotations, develop crop-water relationships, and establish partial enterprise budgets.
Keywords: Forage; Triticale; Sorghum; Oat; Economics; Profit; Rotation